2021
DOI: 10.1128/mra.00563-21
|View full text |Cite
|
Sign up to set email alerts
|

Partial Genome Sequence of a Novel Reo-Like Virus Detected in Asian Citrus Psyllid (Diaphorina citri) Populations from Florida Citrus Groves

Abstract: This report describes the partial (nearly complete) genome sequence of a novel reo-like virus tentatively named Diaphorina citri Cimodo-like virus. This putative virus has 10 double-stranded RNA segments and was detected in Asian citrus psyllid ( Diaphorina citri ) populations collected from Florida commercial citrus groves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…In our HTS analysis, several insect and plant viruses were also assembled and annotated. As in the previous survey [ 15 , 38 ], the Citrus tristeza virus (CTV) seems to commonly exist inside psyllids in four regions explored in this study, but was absent from the grove in Vero Beach, Indian River County. The phenomena suggest that psyllids may easily uptake CTV via phloem-feeding [ 15 ], indicating that D. citri also acts as a potential vector of CTV [ 40 ].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In our HTS analysis, several insect and plant viruses were also assembled and annotated. As in the previous survey [ 15 , 38 ], the Citrus tristeza virus (CTV) seems to commonly exist inside psyllids in four regions explored in this study, but was absent from the grove in Vero Beach, Indian River County. The phenomena suggest that psyllids may easily uptake CTV via phloem-feeding [ 15 ], indicating that D. citri also acts as a potential vector of CTV [ 40 ].…”
Section: Discussionsupporting
confidence: 70%
“…In Florida, Britt et al [ 15 ] completed a comprehensive surveys of psyllid populations in the major citrus production regions of 21 counties. The results demonstrated that all these five viruses and another novel reo-like virus ( D. citri cimodo-like virus, DcCLV) existed in citrus groves [ 38 ], and that DcACV was the most prevalent virus (>60%) followed by DcPLV and DcFLV. Additionally, massive reads related to Citrus tristeza virus (CTV) by RNA sequencing were also found in all sample-collecting regions.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple study articles have provided evidence for the presence of diverse reo-like viruses, such as the Hubei reo-like virus, the French Guiana reovirus, and the Shenzhen reo-like virus [52][53][54]. A recent study documented the discovery of the Diaphorina citri cimodo-like virus within the Asian citrus psyllid insect [55]. Moreover, the cimodo-like virus in brine shrimp has been detected in brine shrimp cyst products from some countries, including Russia, China, Iran, and the United States [56].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, trimmed single-end reads were de novo assembled into contiguous consensus sequences (contigs) using SPAdes version 3.14 with default parameters [ 22 ]. To annotate known viruses, de novo assembled contigs ≥200 bases were compared against a July 2020 copy of the GenBank database from the National Center for Biotechnology Information (NCBI) using BLASTn v. 2.10.1 with a word size of 7 and default parameters [ 23 ]. Finally, for more sensitive identification of viruses within the scope of this study, trimmed reads were aligned to the viral division of the GenBank nucleotide database using bowtie version 2.4.2 [ 24 ] and subsequently processed through PathoScope version 2.0.6 [ 25 ] for absolute read counts for each virus.…”
Section: Methodsmentioning
confidence: 99%